Implementasi Kebijakan Penanggulangan Kebakaran Lahan Gambut di Indonesia: Konflik Pelaksanaan Restorasi Lahan Kawasan Hutan Tanaman Industri - Sarah, Yessi Yolanda (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study was to analyze the implementation of policies and conflicts between actors in restoring peatlands in HTI areas in Riau Province. This research method is qualitative. Secondary data is obtained through literature studies, or from other written sources that do not interact directly with the object of research in order to obtain data. Some of the secondary data used by researchers are documentation and data containing information on the theme of policy implementation, both from electronic and print media. The results of the study show that the inhibiting factors for the achievement of BRG's performance are First, overlapping policies related to the restoration area / map between the executors of activities, namely BRG and KLHK, which causes conflict. Second, coordination between central and local governments in the implementation of restoration so that the Riau Provincial Government is not proactive in supporting the restoration agenda. The Riau Province Environment and Forestry Service does not have a significant role in implementing the peatland restoration agenda in Riau. Third, the inactivity of the Riau Provincial Government is indicated by the fear of disruption to the Industrial Plantation Forest (HTI) and Oil Palm sectors due to peat restoration. This is related to the regional development agenda itself. The disruption of these two sectors has implications for the economy of Riau Province as a whole.